Ocorrência e Significado dos Septos do Embasamento Encontrados nas Suítes Graníticas do Batólito Pelotas, RS, Brasil - PHILIPP, RUY PAULO; MACHADO, RÔMULO (Pesquisas em Geociências, 2002)
<!– .p text-align: justify; –> The Pelotas Batholith situated in the eastern part of Sul-rio-grandense Shield is NE oriented and has dimensions of about 400 x 120 km. It is a granitic belt with six main suites: Pinheiro Machado Suite, Erval Suite, Viamão Suite, Encruzilhada do Sul Suite, Cordilheira Suite and Dom Feliciano Suite. The development of a continental collision whose evolution started by the end of Neoproterozoic, 635-610Ma, and reached 550Ma, is registered in the granitic suites. Most granitoids are syn to late-collisional, which have their emplacement controlled initially by low- to mid-angle shear zones and lately by sub-vertical transcurrent shear zones. The last magmatic events produced alkaline and peralkaline granites and composite (acid and basic) dike swarms represent a postcollisional magmatism.During their ascension and emplacement these granitic units captured basement xenoliths sometimes with dimensions of several kilometers. Based upon petrographic, geochemical and structural data these xenoliths were compared with the metamorphic units that occur outside the batholith. Their similarity suggest that the batholith, in spite of being limited by shear zones, is very close to its original setting. The interaction of xenoliths with the granitic magma produced primary structures that reflect the conditions during the ascent and emplacement of granitic bodies and contribute to the understanding of the geotectonic evolution in the eastern part of Sul-rio-grandense Shield.